Effects of the Lipid Metabolites and the Gut Microbiota in ApoE−/− Mice on Atherosclerosis Co-Depression From the Microbiota-Gut-Brain Axis - Hu, Ke; Liao, Xing-Xing; Wu, Xiao-Yun; Wang, Rui; Hu, Zi-Wei; Liu, Si-Yuan; He, Wen-Fen; Zhou, Jun-Jie (Frontiers in Molecular Biosciences, 2022)
Background: The diagnosis, treatment, and prevention of atherosclerosis co-depression are poor, so it is urgent to explore new targets. Based on the “microbiota-gut-brain axis,” this study aimed to investigate the changes of lipid metabolites in the prefrontal cortex and hippocampus regions and the characteristics of the gut microbiota in ApoE−/− mice with atherosclerosis co-depression. Methods: ApoE−/− mice (hyperlipid feeding combined with binding, HFB group, n = 14, male) fed a high-fat diet for 16 weeks with binding stimulation were used as an animal model for atherosclerosis co-depression. The depression degree of mice was evaluated by body weight, sucrose preference test, open field test, and tail suspension test. Oil-red O staining, HE staining, and biochemical parameters were used to evaluate the damage degree of atherosclerosis in mice. LC-MS/MS technique for non-targeted lipidomics analysis was used to analyze the differential lipid metabolites in the prefrontal cortex and hippocampus regions of mice. 16S rDNA amplification sequencing was used to screen the differential gut microbial, and association analysis was performed with the differential lipid metabolites. Results: Compared with the normal control group (NC group), the HFB group showed depression-like behaviors and atherosclerosis-related pathological indicators. The differential lipid metabolites in the prefrontal cortex and hippocampus regions were mainly LPC, LPE, LPS, PC, PE, PS, PI, and GD1a, and were mainly enriched in the glycerophospholipid metabolism pathway and the retrograde endocannabinoid signaling pathway. At the same time, there were significant differences in the structure of the gut microbial community between the two groups. The abundance of Deferribacteres and Proteobacteria in the HFB group increased, while the abundance of Verrucomicrobia and Actinobacteria decreased at the phylum level; the abundance of Desulfovibrio, Clostridium_IV, Helicobacter and Pseudoflavonifractor increased, while the abundance of Akkermansia decreased at the genus level. Conclusion: Atherosclerosis co-depression of ApoE−/− mice of the prefrontal cortex and hippocampus lipid metabolism pathways of disorder and the changes of to the gut microbiota, which leads to abnormal white matter and synaptic dysfunction, increased gut inflammation, and decreased gut permeability, leading to the release of inflammatory cytokines, there is a strong correlation between both, it further confirmed the existence of the “microbiota-gut-brain axis.”